American sniper [compact disc, unabridged] : the autobiography of the most lethal sniper in U.S. military history - Kyle, Chris, 1974-2013 (Harper Audio, 2012)
The astonishing autobiography of SEAL Chief Chris Kyle, whose record 150 confirmed kills make him the most deadly sniper in U.S. military history.